Energy consideration in pharmaceutical factory layout - Nasry, Nasrul Ashraf; Mahmud, K. S.; Hilmy, Irfan; Ismail, Md Yusof; Basri, R. H. (Asian Research Publishing Network (ARPN), 2015)
This paper focuses on energy consumption in a pharmaceutical industry. The efficient energy consumption depends on energy layout planning. Materials handling consideration may save the energy. The wastage of energy resources leads to wastage of money. The proposed new layout has been designed for the company X for energy efficiency. The energy efficiency calculation is based on total weekly energy usage in the company X. After the research, the work flow analysis can be planned for ease material handling. The saving of the energy consumption leads in saving 20% of electricity bills. In the other way, it save money and environment friendly because energy consumption used is less